Gamifikasi untuk Pembelajaran - Diana Ariani (Universitas Negeri Jakarta, 2020)
Gamification is a method that is currently slowly but surely starting to be looked at to be developed together with the e-learning Learning Management System (LMS). However, the nature of gamification in learning is still not widely known by many parties. This article will try to explain some important things you need to know to develop Gamification. Some of the things that will be discussed in this article are the definition of gamification, the basic elements of gamification, the types of gamification, and the implementation of Gamification and LMS E-learning.